Management of Anti-Corruption Education in The Context of Instilling Moral Values In Schools - Ilham Andika Putra; Achadi Budi Santosa (JURUSAN MANAJEMEN PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI GORONTALO, 2024)
Anti-corruption education (ACE) is an important part of character education, but its application is often neglected. The purpose of this study is to reveal the implementation of ACE in Indonesia, where character education has been regulated through the 2013 curriculum. The research was conducted through a qualitative approach to the narrative literature review model. The results of the study show that the implementation of ACE still requires various important preparations, including; (1) schools need to prepare a team of educators who have particular responsibility in developing ACE values, (2) inculcating ACE local content in learning activities, this can be done through motivation and regular religious moral development, (3) the application of ACE needs to be integrated in the eyes general lessons, (4) it is necessary to prepare a conducive social environment, so that the implementation of ACE in schools can be realized in the lives of students in society. The implication is that support from the government and the community is needed to create a conducive environment to support the ACE planting process.